2020
DOI: 10.1017/s0022215120001899
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal sound localisation and speech perception in Bonebridge-implanted single-sided deafness patients

Abstract: Objective This study aimed to investigate the benefit of Bonebridge devices in patients with single-sided deafness. Method Five patients with single-sided deafness who were implanted with Bonebridge devices were recruited in a single-centre study. Participants’ speech perception and horizontal sound localisation abilities were assessed at 6 and 12 months post-operatively. Speech intelligibility in noisy environments was measured in three different testing conditions (speech and noise pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…6 b). This outcome is comparable to the average improvements reported for the BCI 601 in a similar setup (S SSD N0°), with a range of + 0.3 to − 2.5 dB [ 11 , 40 , 53 , 61 64 ].…”
Section: Discussionsupporting
confidence: 83%
“…6 b). This outcome is comparable to the average improvements reported for the BCI 601 in a similar setup (S SSD N0°), with a range of + 0.3 to − 2.5 dB [ 11 , 40 , 53 , 61 64 ].…”
Section: Discussionsupporting
confidence: 83%
“…Future studies involving larger cohorts are warranted to provide more comprehensive insights in this area. Notably, Zhao et al showed great improvements in SNR and sound localization in patients with SSD 58 …”
Section: Discussionmentioning
confidence: 99%
“…For UAA, instead, surgical repair may not always result in a significant improvement in hearing [31,32], and revision surgeries are commonly needed [33][34][35]. Therefore, BAHD (on soft-band, or adhesive adapter [36], as well as with percutaneous or transcutaneous abutment), the Vibrant Bonebridge (MED-EL GmbH) [37,38], the Vibrant Soundbridge (MED-EL GmbH, Innsbruck, Austria) [39], and the Osia II (Cochlear Corp., Sydney, Australia) [40,41] have also been offered to children with UAA, with the aim of providing binaural hearing [42,43]. Even in UAA cases, RM can provide hearing relief, especially in difficult situations such as a scholastic setting.…”
Section: Introductionmentioning
confidence: 99%